The development of inpatient cost and nursing service weights in a tertiary hospital in Malaysia - Nor Haty Hassan; Syed Mohamed Aljunid; Amrizal Muhammad Nur (BMC, 2020)
Abstract Background The current healthcare sector consists of diverse services to accommodate the high demands and expectations of the users. Nursing plays a major role in catering to these demands and expectations, but nursing costs and service weights are underestimated. Therefore, this study aimed to estimate the nursing costs and service weights as well as identify the factors that influence these costs. Methods A retrospective cross-sectional descriptive study was conducted at Universiti Kebangsaan Malaysia Medical Centre (UKMMC) using 85,042 hospital discharges from 2009 to 2012. A casemix costing method using the step-down approach was used to derive the nursing costs and service weights. The cost analysis was performed using the hospital data obtained from five departments of the UKMMC: Finance, Human Resource, Nursing Management, Maintenance and Medical Information. The costing data were trimmed using a low trim point and high trim point (L3H3) method. Results The highest nursing cost and service weights for medical cases were from F-4-13-II (bipolar disorders including mania - moderate, RM6,129; 4.9871). The highest nursing cost and service weights for surgical cases were from G-1-11-III (ventricular shunt - major, RM9,694; 7.8880). In obstetrics and gynaecology (O&G), the highest nursing cost and service weights were from O-6-10-III (caesarean section - major, RM2,515; 2.0467). Finally, the highest nursing cost and service weights for paediatric were from P-8-08-II (neonate birthweight > 2499 g with respiratory distress syndrome congenital pneumonia - moderate, RM1,300; 1.0582). Multiple linear regression analysis showed that nursing hours were significantly related to the following factors: length of stay (β = 7.6, p < 0.05), adult (β = − 6.0, p < 0.05), severity level I (β = − 3.2, p < 0.05), severity level III (β = 7.3, p < 0.05), male gender (β = − 4.2, p < 0.05), and the elderly (β = − 0.5, p < 0.05). Conclusions The results showed that nursing cost and service weights were higher in surgical cases compared to other disciplines such as medical, O&G and paediatric. This is possible as there are significant differences in the nursing activities and work processes between wards and specialities.